Pemberdayaan Kelompok Tani dalam Meningkatkan Produksi Tomat dengan Pemanfaatan Agensia Hayati Streptomyces s p.,& Trichoderma sp - Suryaminarsih, Penta; Haryani, Wiwik Sri; Mujoko, Tri (Berkala Ilmiah AGRIDEVINA, 2016)
Pare farmer generally cultivatetheirfood crop andhorticulture to gain sallary. Planting pattern to be useispaddy–maize–maize. That cultivation area utilizewith tomato and chili, andothervegetables i.e. :eggplant, long beans, squash, honeydrew and othervegetables. In term of increase productivity,thefarmer utilizeexaggerate chemicalpesticide andfertilizer.Meanwhile there is no attentionforexaggeratechemicalpesticide andfertilizerimpact toenvironment and customers.Research goal is toutilization ofStreptomycessp.,Trichodermasp.asdecomposer andbiological agent to increaseproductionand decrease farmer’s dependency tochemical fertilizer and pesticide. The method useactive farmer’s participant (PAR) as well asdemoplot. Farmer’s group multiply and implementbiological agent to tomato and chili. Reduce chemicalfertilizer up to 50%. Number of active farmer’s groupdevelop and utilize biological agent up to 30%.Farmer’s observation show thatpest and disease aswell as growing plant almost similar with commonpractice. Average production of tomato 25 Kg/harvestwith harvesting time upto 25. Then averageproduction of chili up to 10 Kg/harvest with harvestingtime up to 3.Keyword :Biologizal agent, PAR, Demplot, Decomposer